Ośrodki tworzenia efektywności na rynku systemów ratalnych - Zajkowski, Robert (Centres of efficiency creation on the instalment systems market, 2008)
The paper presents mechanisms of finansial efficiency formation at the instalment systems segment of the financial brokerage market. Typical dirctions of the sector business effects distribution are pointed out as well as directions of financial resources flows between firms. The paper also presents differences in cost structure (payments, commissions, interest, rates) of typical bank credit and instalment system credit.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 463-473